A case of disseminated tuberculosis mimicking metastatic cancer. (2018) - Chamberlin, K.; Orfanos, S.; Mukherjee, A.; Moy, E.; Koganti, M.; Khan, W.
Abstract: Background: Disseminated tuberculosis (TB) or miliary TB is defined as lymphohematogenous dissemination of Mycobacterium tuberculosis bacilli, which may then affect virtually any organ system. The multiple organ involvement in disseminated TB can mimic metastatic cancer and can make the diagnosis challenging. False negatives are common therefore repeating microbiologic and histologic samples is essential. Case report: We report the case of a young immunocompetent patient presenting with multiple atypical extra-pulmonary TB involvement. The patient presented with pulmonary, pleural, bilateral testicular and multiple bone involvement including calcanerium abscesses. These lesions were initially described as metastasis by the radiologist. Therefore lymphoma and metastatic testicular cancer as well as TB were high on the differential in this young foreign-born male. Pleural, broncho-alveolar lavage, bone marrow and cerebrospinal fluid acid-fast bacilli smear and microbiologic culture were all negative. However the histologic examination of the trans -bronchial biopsy and pleural biopsy showed necrotizing granuloma and helped to narrow down the diagnosis. The patient improved with RIPE therapy. Conclusion: This case illustrates the diagnostic difficulty of disseminated TB with atypical organ involvement. Culture is the gold standard for diagnosing TB but is a long process and with 23% of culture negative TB in the United-States, the diagnosis sometimes relies on thoroughly ruling-out differential diagnosis and histologic examination.